Evaluation of cell sorting aerosols and containment by an optical airborne particle counter. (26th May 2015) - Xie, Mike; Waring, Michael T.
Abstract Understanding aerosols produced by cell sorting is critical to biosafety risk assessment and validation of containment efficiency. In this study an Optical Airborne Particle Counter was used to analyze aerosols produced by the BD FACSAria and to assess the effectiveness of its aerosol containment. The suitability of using this device to validate containment was directly compared to the Glo‐Germ method put forth by the International Society for Advancement of Cytometry (ISAC) as a standard for testing. It was found that high concentrations of aerosols ranging from 0.3 µm to 10 µm can be detected in failure mode, with most less than 5 µm. In most cases, while numerous aerosols smaller than 5 µm were detected by the Optical Airborne Particle Counter, no Glo‐Germ particles were detected, indicating that small aerosols are under‐evaluated by the Glo‐Germ method. The results demonstrate that the Optical Airborne Particle Counter offers a rapid, economic, and quantitative analysis of cell sorter aerosols and represents an improved method over Glo‐Germ for the task of routine validation and monitoring of aerosol containment for cell sorting. © 2015 International Society for Advancement of Cytometry